Hubungan Stres Kerja Dengan Produktivitas Kerja Pada Perawat Di Ruang Rawat Inap - Zahalim; Nawawi; Prawara Aros Purnama; La Ode Ardiansyah (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
Productivity is the ability of nursing staff to carry out their duties and responsibilities so as to produce performance that can contribute directly to improving the quality of hospital services. Less productive nursing services will reduce the quality of services provided to patients. Job stress is one of the factors that affect the work productivity of nurses in the inpatient ward. Nurses who are stressed in the work of nurses in the inpatient ward are often caused by excessive workload, lack of training and improvement of nurse competencies, lack of communication and reward systems that have an impact on nurse work productivity. The purpose of this study was to determine the relationship between job stress and nurse work productivity in the inpatient ward of Bahteramas Regional Hospital. This study used observational analytic with cross-sectional study design. The population in this study was 263 respondents, using proportion sampling technique with a sample size of 72 respondents. The analysis method used chi-square test and Cramer's. The results of the study obtained a value ( =5.501, and a P-value of 0.001 which means significant and the results of the Cramer's test=0.276) which means there is a weak correlation between job stress and work productivity. It is expected that Hospital management will conduct an analysis of the need for nursing staff in inpatient rooms, conduct open communication between superiors and subordinates, provide training and capacity development for nurses, and improve the reward system for nurses who excel and carry out their duties responsibly.